Lifetime trauma victimization and PTSD in relation to psychopathy and antisocial personality disorder in a sample of incarcerated women and men. Issue 2 (15th June 2015) - Gobin, Robyn L; Reddy, Madhavi K.; Zlotnick, Caron; Johnson, Jennifer E.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Antisocial personality disorder (ASPD) and psychopathy are similar, but distinct, psychiatric conditions that are common in male and female inmates; a segment of the population with high rates of trauma exposure. It is unclear whether specific types of lifetime trauma are associated with ASPD and psychopathy in incarcerated women and men. Furthermore, the unique roles of post-traumatic stress disorder (PTSD) symptom severity and trauma victimization in antisocial personality disturbance are not well-understood. The paper aims to discuss these issues. Design/methodology/approach – This study investigated associations between trauma variables (different kinds of traumatic experiences and PTSD) and antisocial personality variables (ASPD and psychopathy) in a sample of incarcerated women and men who participated in a randomized clinical trial for major depressive disorder. In total, 88 incarcerated men and women were assessed for ASPD diagnosis, psychopathy severity, PTSD symptom severity, and history of physical, sexual, and crime-related trauma. Regression analyses predicted ASPD or psychopathy from trauma variables, controlling for gender. Findings – Physical trauma was the only form of trauma that was significantly related to psychopathy. Physical trauma and crime-related trauma were associated with ASPD. PTSD symptom severity was not associated with psychopathy or ASPD. Originality/value – There are associations between some kinds of lifetime trauma exposure and current ASPD/psychopathy in the target sample, but these associations do not appear to be mediated through current PTSD symptoms.